Sustainable Marketing Strategies for SMEs: The Impact of Customer Engagement on Business Growth in the Context of Environmental Sustainability - Sudi, Didih Muhamad (ADMAN: Journal of Contemporary Administration and Management, 2024)
As a crucial segment in the economy, SMEs face unique challenges and opportunities in implementing sustainable marketing strategies. Amid growing awareness of the environmental impacts of business activities, SMEs are expected to adapt to practices that support environmental sustainability while driving their business growth. This study aims to identify and analyze the most effective sustainable marketing strategies for SMEs and how customer engagement influences their business growth. The study employs a literature review method with a qualitative approach. Research data were sourced from Google Scholar, focusing on publications between 2017 and 2024. The findings of this study demonstrate that implementing sustainable marketing can have a significant positive impact on the business growth of SMEs in the context of environmental sustainability. SMEs can enhance customer attraction and loyalty, as well as strengthen their brand reputation by integrating sustainability principles into their marketing strategies. Case studies such as Kopi Kita and Batik Keris affirm that adopting eco-friendly practices can improve SMEs' market positioning in an increasingly environmentally conscious marketplace.